Malathion-Induced Changes in Gill and Intestinal Esterase Banding Patterns of Labeo rohita - Mandalapu, Venkateswara Rao; Yanamala, Venkaiah (Contemporary Research and Perspectives in Biological Science Vol. 5, 2024)
Contamination of surface waters has been well documented worldwide and constitutes a major issue at local, regional, national, and global levels. In fish, different insecticides can be absorbed through gills, skin or alimentary ducts. Fishes are particularly sensitive to environmental contamination of water. Hence, pollutants such as insecticides may significantly damage certain physiological and biochemical processes when they enter into the organs of fishes. The present study was undertaken to assess the toxicological effect of Malathion (an Organophosphate) on electrophoretetic banding patterns of esterase enzymes in gill and intestine tissues of freshwater fish Labeo rohita (Hamilton) at different time intervals i.e. 24H, 48H, 72H and 96H and was compared with control. The esterase isozymes were quantitatively analyzed by using 7.5% native polyacrylamide gel electrophoresis (PAGE) stained with \(α\)-naphthyl acetate as substrate. Three different esterase enzyme bands were detected and named Est-1; Est-2 and Est-3 with different relative mobilities such as 0.6± 0.05; 0.4± 0.05; 0.3± 0.05 in gill and intestine tissue. All three esterase bands were found in the gill and intestine tissues in control. Isoenzyme pattern exhibits differences in the various fish populations and is also used to develop a genetic sexing system. The banding pattern of esterases of different tissues has a good potential used in the identification of species. After the fish is exposed to Malathion (an Organophosphate), in gill tissue Esterase-1 showed resistance, Esterase-2 and Esterase-3 were severely affected, whereas Esterase-3 were severely affected than Esterase-2 and Esterase-1 exhibited resistance in Intestine tissue. The present study reported that the expression of tissue-specific esterase isozymes showed a differential banding pattern that could be used in toxicological studies and also could be used for the development of molecular markers for the identification of different species of fish. This present study helps in finding a proper solution for aquatic ecosystem pollution that occurs due to pesticides. Research has to continue to find alternatives for OP compounds in agriculture.